In a novel landscape, in the Eastern Cape, South Africa, what are the key vegetation resources that support livestock production? - Liversage-Quinlan, William Peter (Rhodes University, Faculty of Science, Institute for Water Research)
The Tsitsa River is the largest remaining river that is without a dam in South Africa, and so the government has pledged to install two major dams for irrigation and hydroelectricity, under the Mzimvubu Water Project. These dams are intended to supply water and electricity to surrounding communities as well as the large neighbouring urban areas of Mthatha and Tsolo. However, large areas of the Tsitsa Catchment (~494 000 ha) are degraded, posing the possibility that if these dams were to be created, they would inevitably fill with sediment and silt within a few decades. To address these issues, the Tsitsa Project was established in 2014 to co-ordinate actions by government, developers and local communities in order to restore the landscape condition and prevent soil erosion, as well as to improve the livelihoods of the people who live there (Fabricius, Biggs, & Powell, 2016). Research into the landscape condition as well and the environmental interactions with local communities are therefore highly necessary in order to guide restoration practices to their best effect. The economic necessity for livestock production in the catchment indicates its urgent need for a better understanding of its current effects on the catchment landscape and vegetation. The overall goal of this study is to contribute to the knowledge needed to manage the area in a sustainable way. This paper will therefore examine the key vegetation resources that support livestock production in an area of the Tsitsa River Catchment, by describing the various types that exist, and by determining their relative production levels of usable livestock forage.
Keywords: Mzimvubu River Watershed (South Africa); Livestock productivity -- South Africa Mzimvubu River Watershed; Range ecology -- South Africa Mzimvubu River Watershed; Land degradation -- South Africa Mzimvubu River Watershed; Vegetation dynamics -- South Africa Mzimvubu River Watershed; Novel landscapes